(untitled) (Bangladesh Journal of Pharmacology, 2014)
Antimicrobial evaluation of methanol extract of Sarcochlamys pulcherrima leaf and its hexane, ethyl acetate, n-butanol and water fractions against 31 strains of microorganisms, using agar well, agar disc diffusion, and broth microdilution methods, revealed the activity of methanol extract against Trichophyton mentagrophytes, Candida albicans, Staphylococcus aureus and Escheracia coli (zone of inhibition: 21-40 mm, 200 mg/mL, and MIC: 6.25-50 mg/mL). All fractions also displayed antimicrobial activity (5-20 mg/mL), indeed ethyl acetate and n-butanol fractions showed better activity (MIC: 0.156 to 2.5 mg/mL). C. albicans was most sensitive to n-butanol fraction (15 mm, 2.5 mg/mL). Ethyl acetate and n-butanol fractions were more active against T. mentagrophytes (12 mm at 1.25 mg/mL) and S. aureus (ethyl acetate-16 mm, n-butanol-14 mm at 0.625 mg/mL). E. coli was inhibited by n-butanol fraction (13 mm at 2.5 mg/mL). Further, n-butanol fraction (400 µg/disc) exhibited promising activity against 14 bacteria, 2 dermatophytes and 2 yeasts strains.